2007
DOI: 10.1038/sj.ejcn.1602735
|View full text |Cite
|
Sign up to set email alerts
|

Development of a scale to measure 9–11-year-olds' attitudes towards breakfast

Abstract: Objective: Development and validation of a questionnaire to measure children's attitudes towards breakfast. Design: A pilot study was used to select questionnaire items and assess test-retest reliability. The questionnaire was then administered to a larger sample of children together with a dietary recall questionnaire. Randomly selected subsets of these children also completed a dietary recall interview or their parents were asked to complete a questionnaire relating to their child's breakfast eating habits. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 35 publications
(58 reference statements)
3
26
2
Order By: Relevance
“…A survey conducted in 2495 fifth and sixth grade children also found that those who did not skip breakfast displayed more positive attitudes than children who skipped breakfast. In addition, more positive attitudes toward breakfast were significantly correlated with consumption of a greater number of 'healthy' foods for breakfast (that is, fruit, bread, cereal and milk products), consumption of fewer 'unhealthy' foods for breakfast (that is, sweet items and crisps) and parental perceptions that their child usually ate a healthy breakfast (Tapper et al, 2008). A study that investigated associations of daily breakfast consumption with demographic and lifestyle factors in 41 countries, including 4610 children from Israel, found that daily breakfast among 11-, 13-and 15-year olds was consumed by 35% of the girls and 43% of the boys, results as low as the percents reported in the United States (Vereecken et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A survey conducted in 2495 fifth and sixth grade children also found that those who did not skip breakfast displayed more positive attitudes than children who skipped breakfast. In addition, more positive attitudes toward breakfast were significantly correlated with consumption of a greater number of 'healthy' foods for breakfast (that is, fruit, bread, cereal and milk products), consumption of fewer 'unhealthy' foods for breakfast (that is, sweet items and crisps) and parental perceptions that their child usually ate a healthy breakfast (Tapper et al, 2008). A study that investigated associations of daily breakfast consumption with demographic and lifestyle factors in 41 countries, including 4610 children from Israel, found that daily breakfast among 11-, 13-and 15-year olds was consumed by 35% of the girls and 43% of the boys, results as low as the percents reported in the United States (Vereecken et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Both questionnaires are relatively quick to administer and simple to score. These qualities make it ideal for use in which validity at the individual level is important or in which more timeconsuming dietary measures are not feasible (Tapper et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Step 29 . In terms of individual food categories, associations with attitudes were strikingly similar to those observed for deprivation, although with the direction of correlations inverted.…”
Section: Discussionmentioning
confidence: 99%
“…Data for the present study are derived from the evaluation of the Welsh Assembly Government's Free School Breakfast Initiative 11 . A recent study focusing upon a sub-sample from this evaluation found that, amongst children aged 9-11 years, attitudes towards eating breakfast were significantly associated with the likelihood of skipping breakfast 29 . Furthermore, attitudes were associated with the quality of breakfast consumed, in that they were positively correlated with the total number of fruits, bread, cereals and milk products consumed and negatively correlated with the total numbers of sweet items and crisps.…”
mentioning
confidence: 99%